A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 4 years ago
\[\left\frac{1}{a^2}\frac{1}{b^2}\right\leq\frac{2ab}{k^3}\]where\[a,b>k>0\]
anonymous
 4 years ago
\[\left\frac{1}{a^2}\frac{1}{b^2}\right\leq\frac{2ab}{k^3}\]where\[a,b>k>0\]

This Question is Closed

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0\[\left\frac{1}{a^2}\frac{1}{b^2}\right=\left\frac{b^2a^2}{(ab)^2}\right=\frac{a^2b^2}{(ab)^2}=\frac{(ab)(a+b)}{(ab)^2}\leq\frac{aba+b}{k^4}\]now, all i have to prove is\[a+b\leq2k??\]

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0i dont know where ive gone wrong if at all _

watchmath
 4 years ago
Best ResponseYou've already chosen the best response.0do we know the relation between a and b?

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0it just says \(a,b>k>0\) :(\[\]

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0ah damn i forgot there was a 2 in the numerator...

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0You must make an assumption. Lets do two cases: \[C1 \rightarrow a>b>k; C2 \rightarrow k<a<b; C3 \rightarrow a=b>k\] What can we say based off these assumptions? Well for the first one. We would then have that: \[\frac{1}{a^2}\frac{1}{b^2}<0 \implies \left\frac{1}{a^2}\frac{1}{b^2} \right=\frac{1}{b^2}\frac{1}{a^2}\] By the definition of absolute value. Since they are positive that means that ab>0 so ab=ab by def. Leaves us with: \[\frac{1}{b^2}\frac{1}{a^2} \le ^? \frac{2(ab)}{k^3}\] Since k>0 we can multiply by k^3 and divide by 2 giving: \[\left( \frac{1}{b^2}\frac{1}{a^2} \right)\frac{k^3}{2} \le^?(ab); \forall a>b>k>0?\] Getting a common denominator and doing some algebra gives: \[\frac{a^2b^2}{b^2a^2}\frac{k^3}{2} \le^? (ab) \implies \frac{k^3}{2}\le(ab)\] We KNOW this is true because: \[a,b,k>0 \implies (ab),k^3>0\] So now we have reached a fact that we know is TRUE! Now you must REVERSE the logic and argue why, starting with what we just derived that we know as FACT!!!, and argue why the initial is true. Think about it, you can start with something that is false and derive something true, you must start with something you know is true (the last bit) and use logic to get back up. I hope this helps, the other cases are similar.

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0The bottom should be a^2b^2 not b^2a^2, so that changes it a bit...hmmm...lets go from there: \[\frac{a^2b^2}{a^2b^2}\frac{k^3}{2} \le^?(ab) \implies \frac{(ab)(a+b)}{a^2b^2}\frac{k^3}{2} \le^? (ab)\] Divide out the ab giving (since a>b implies ab=/=0) \[\frac{a+b}{a^2b^2}\frac{k^3}{2} \le^? 1\] \[a+b \le^? \frac{2a^2b^2}{k^3}\] I think from here we can argue. Because a,b>0 so and a>b>k>0 so a^2b^2 should always beat out k^3... I'm not sure, its something simliar lol
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.